Penerapan Dan Pelatihan Strategi Pemasaran Digital Di Sellindo Shop - Diana Diana (Universitas Internasional Batam, 2021)
The purpose of this study is to measure the effectiveness of digital marketing strategy that applied to a mobile shop SME in Batam. The SME had never used digital marketing before, but interested to try after the Covid-19 pandemic affected their sales. The method used in this study involved observation, interview, literature study, and documentation study. The output of the study including: social media account for business on Instagram, Tokopedia account, promotion video, and influencer marketing. This result shows that the uses of social media and influencer marketing actively affected the sales on SME, but the effectiveness of e-commerce marketing was not proven in this study. Thus, we would recommend doing more research on e-commerce marketing effectiveness to increase the sales in related business.